RETRACTED: Data distribution and asymmetry in leaf blade Prunus padus L. - Baranov Sergey; Zykov Igor; Prokopenko Aleksandra; Fedorova Lubov; Lipponen Irina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001